Analysis of Rainwater Acidity in Semarang City - Sri Wulan Siti Khotijah; Sri Endah Ardhi Ningrum Abdullah; Abdul Latif; Sunarno; Dwi Atmoko (Universitas Negeri Semarang, 2026)
Rainwater is the result of the evaporation process that condenses and falls to the earth's surface. On its way, rainwater mixes with dust particulates and greenhouse gases such as carbon dioxide (CO2), carbon monoxide (CO), sulfur dioxide (SO2), nitrogen dioxide (NOx), nitrous oxide (N2O), methane (CH4), and other hydrocarbons. This mixture can produce acid rain if the pH of the rainwater is below 5.6. Analyzing the potential for acid rain in urban areas is important as an early detection measure of potential environmental damage. In Semarang City, which has high traffic density and industrial areas, this study examined the acidity of rainwater during the period 2016-2023. The primary data used were rainwater pH data and chemical compounds from the BMKG Air Quality Testing Laboratory. The data were analyzed descriptively to determine the level of acidity and the content of chemical compounds in rainwater. The results showed that the frequency of acid rain in Semarang peaked in 2020 with 83.3%. Strong acid compounds, such as SO4, NO3, and Cl, dominate the chemical content of rainwater with an average of 62.4%, while strong bases and weak bases are 28.7% and 8.9%, respectively. SO4 and NO3 compounds, which originate from motor vehicle emissions, are the main components determining acid rain in this region. This study provides an important rationale for mitigating and preventing the negative impacts of acid rain in Semarang City